Employing Poland's Military Depolitization and Professionalism As Security Sector Reform Strategy For Indonesia - Fathomi Abdillah Safi (Dinasti Research, 2024)
This article examines the reform of Poland’s security sector and its relevance for Indonesia. The study focuses on the depoliticization and professionalization of the Polish military. Depoliticization aims to remove political party influence from the military and ensure civilian control over strategic and defense decisions. This involves reducing political roles within the military, reforming military education, and establishing an independent legal framework. Professionalization has been achieved by modernizing technology and weaponry, enhancing soldier skills to meet NATO standards, and participating in joint exercises with NATO allies. These efforts have improved the effectiveness and efficiency of the Polish military in maintaining national security and regional stability. Using qualitative methods and Creswell’s comparative study approach, the research highlights how Poland’s experience can guide Indonesia in its military reforms. By integrating depoliticization and professionalization strategies inspired by Huntington and Stephan, the article provides a framework to accelerate and improve military reform in Indonesia.